The Soteriologies of Karl Rahner and Hans Urs Von Balthasar - Fischer, Mark F. (Philosophy & theology, 2016)
Karl Rahner and Hans Urs von Balthasar differed in their approaches to Christian soteriology, especially in their understandings of redemption and the cross. These differences stem in part from Rahner’s emphasis on the Trinity in history (the economic Trinity) and Balthasar’s focus on the Trinity’s inner life (the immanent Trinity). While Balthasar’s soteriology better reflects the Church’s official descending Christology, Rahner’s ascending Christology (with its view of Jesus as the fullness of God united to human nature) is the more profound.